HKA Angle—A Reliable Planning Parameter for High Tibial Osteotomy: A Theoretical Analysis Using Standing Whole-Leg Radiographs - Jiang, Xu; Xie, Kai; Han, Xuequan; Ai, Songtao; Wu, Haishan; Wang, Liao; Yan, Mengning (The Journal of Knee Surgery, 2020)
High tibial osteotomy (HTO) is a recognized treatment for early-stage medial compartment knee osteoarthritis. Preoperative planning with standing whole-leg radiographs (WLRs) is essential for ensuring optimal postoperative alignment. The primary purpose of this study is to investigate the theoretical accuracy of the wedge opening required for two different preoperative planning parameters in open-wedge HTO. The second purpose is to theoretically determine which parameter is superior. Preoperative planning for HTO was performed with standing WLRs for 39 knees with isolated medial osteoarthritis. The Miniaci preoperative planning method was applied to correct the hip-knee-ankle (HKA) angle to 3to 6 degrees of valgus and the weight-bearing line (WBL) percentage within 60 to 70% of the width of the tibial plateau. To ensure that the HKA angle was between 3 and 6 degrees of valgus, the required accuracy window for the Miniaci angle was 3.25 ± 0.03 degrees (range, 3.20–3.30°). To ensure that the WBL percentage was between 60 and 70%, the accuracy window required for the Miniaci angle was 2.35 ± 0.13 degrees (range, 2.10–2.65°). This study suggests that to correct the HKA angle and the WBL percentage within the target range on two-dimensional WLRs, the Miniaci angle must be controlled to an accuracy of ± 1.63 and ± 1.18 degrees, respectively. Theoretically, the HKA angle is highly suitable as a preoperative planning parameter for HTO with a large permissible error and a small variability in the degree of change in the Miniaci angle (ΔMiniaci).
Keywords: osteoarthritis; high tibial osteotomy; accuracy; preoperative planning; alignment parameter